Szkieletowy system ekspertowy w procesie prognozowania doskonalenia produktu - Kiełtyka, Leszek; Jędrzejczyk, Waldemar (Frame expert system in product improvement prognosis process, 2006)
This paper presents the issues of factors conditioning enterprise’s success on the market. Basicfeatures of expert systems, particularly in reference to prognostic issues, are outlined in it. The process of prognostic model construction by means of frame expert system is presented in the paper on the example of problem analysis concerning product improvement. Sphinx package is used as a base.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 341-349